Eminepygia myanmarensis sp. nov., a new Earwig (Dermaptera) Nymph in Burmese Amber - Chen, Xin-Yu; Zhang, Hua-Chuan (Zootaxa, 2021)
A new fossil earwig nymph, Eminepygia myanmarensis gen. et sp. nov. (Pygidicranidae), from the mid-Cretaceous amber of Myanmar, is described and figured. Eminepygia myanmarensis gen. et sp. nov. can be readily distinguished from all other extinct and recent members of Dermaptera by the prominent bulges on the last three terga. Our new finding sheds further light on the diversity and morphological disparity of fossil dermapterans during the Late Mesozoic.